Tingkat Kepuasan Konsumen Cafe Bifi Coffee Kelurahan Pondang Kecamatan Amurang Timur Kabupaten Minahasa Selatan - Tambajong, Romario; Benu, Noortje Marselianie; Pangemanan, Lyndon Reinhardt Jacob (AGRI-SOSIOEKONOMI, 2023)
This study aims to determine the level of customer satisfaction of Bifi Coffee, Pondang Village, East Amurang District, South Minahasa Regency. The research was conducted from May to July 2023. This study uses accidental sampling technique, namely determining the sample by chance, that is, anyone who happens to meet the researcher can be used as a sample. Determination of the sample using the Malhora formula, namely 5 multiplied by the number of variables or the number of questions available, with 13 question indicators, the sample taken was 65. The results showed that the attributes that need attention and are the top priority for improvement are quadrant I (ease of responding to requests and attractive place decoration). In the next attribute included in quadrant II (alertness of employees when customers visit, courtesy to customers, friendliness to customers, cleanliness and tidiness of the place, available equipment facilities and tidiness of service appearance). Attributes that fall into quadrant III (employee skills and abilities, timeliness in serving and ease of communication). Quadrant IV attributes (speed of the presentation process, readiness and willingness to serve customers). Based on the CSI calculation, the value of the level of customer satisfaction at Cafe Bifi Coffee, Pondang Village, East Amurang District, South Minahasa Regency reaches a value of 80.71%. This value is in the range 0.66-0.80%, thus overall consumers are satisfied with Cafe Bifi Coffee.